MENUMBUHKAN KREATIVITAS ANAK TUNARUNGU DALAM KEGIATAN PENGEMBANGAN DIRI SENI TARI DI SLB NEGERI 2 PADANG - Sri Nurbayani; Yuliasma Yuliasma; Afifah Asriati (SENDRATASIK UNP, 2017)
AbstractThis research is initiated by the lack of creativity of deaf childern in self development activities of dancing classat SLB Negeri 2 Padang at the beginning of the researcher’s observation. It was found that the children only imitated, followed and memorized the movement taught by the teacher.  Therefore, the teacher made some efforts to cultivate the creativity of deaf children. The purpose of this research was to describe the teacher’s way to foster the children’s creativity in self-development activities of dancing class at SLB Negeri 2 Padang. The type of this research was qualitative research using descriptive method. The objects of this research were 5 deaf children in self development activities of dancing art at SLB Negeri 2 Padang. The data were collected through interviews and observations. After that, the data were analyzed through data collection, data reduction, data presentation, and conclusions. The findings of the research are: 1. Teacher's efforts to foster the creativity of deaf students were as follow: a) to use visual stimuli, b) to guide exploration, and c) to provide reinforcement. 2. The improvement of student creativity had an impact on: a) students’ concentration, b) the emergence of students’ self-confidence, and c) students' dancing abilities. Through the visual stimulation, the children were able to explore the movement guided by the teacher, to adjust the calculation, to memorize the motion and to adjust to the accompaniment. Students are able to create simple movements and able to develop them into several movements. Students were able to demonstrate the dance with a variety of movements in accordance with the level of their motor skills as well as to build a good concentration in receiving the dance materials. Students were more confident and enthusiastic because of the reinforcement given by the teacher. Students showed high enthusiasm in creating movements according to the creative imagination through guidance from the teacher. Keywords: Creativity, Deaf, Dance Self Development.